As práticas alimentares: semelhanças entre os cardápios da elite imperial e os restaurantes da cidade de Belém no século XIX (1870 – 1889) - SOUSA, Ellem Cristina de Sousa e (2023)
In the second half of the 19th century, Brazil began a transformation of eating habits and customs influenced by Europe, where having richer foods was synonymous with a new standard of sociability and good taste. The city of Belém, as a result of the golden period of the Rubber Cycle, occupied an important position, due to its port, which was supplied by native and imported products. Under this conjuncture, this research proposes to understand the existing connections between the imperial menus of the second half of the 19th century and the menus of the restaurants in the city of Belém described in the newspapers from 1870 to 1889. From this analysis, it is intended to identify the eating habits of the Brazilian imperial elite's lunches and dinners and understand to what extent the city of Belém adopted eating habits that already existed in the Imperial Court.